I am the messenger - Zusak, Markus (New York : Knopf, 2005)
After capturing a bank robber, nineteen-year-old cab driver Ed Kennedy begins receiving mysterious messages that direct him to addresses where people need help, and he begins getting over his lifelong feeling of worthlessness. Meet Ed Kennedy underage cabdriver, pathetic cardplayer, and useless at romance. He lives in a shack with his coffee-addicted dog, the Doorman, and he's hopelessly in love with his best friend, Audrey. His life is one of peaceful routine and incompetence, until he inadvertently stops a bank robbery. That's when the first Ace arrives. That's when Ed becomes the messenger. Chosen to care, he makes his way through town helping and hurting (when necessary), until only one question remains: Who's behind Ed's mission? Winner of the 2003 Children's Book Council Book of the Year Award in Australia, I Am the Messenger is a cryptic journey filled with laughter, fists, and love.
Originally published: Australia : Pan Macmillan Australia, 2002, as The messenger.
640
Keywords: Self-esteem -- Juvenile fiction; Heroes -- Juvenile fiction; Taxicab drivers -- Juvenile fiction; Self-esteem -- Fiction; Heroes -- Fiction; Taxicab drivers -- Fiction